2023
DOI: 10.3390/molecules28031221
|View full text |Cite
|
Sign up to set email alerts
|

μ-Raman Determination of Essential Oils’ Constituents from Distillates and Leaf Glands of Origanum Plants

Abstract: A novel, inexpensive and simple experimental setup for collecting μ-Raman spectra of volatile liquids in very small quantities was developed. It takes advantage of capillary forces to detain minute volatile liquid volumes. Spectra of volatile and even scattering or absorbing media can be measured more effectively. The method is used to facilitate the collection of intensity-consistent Raman spectra from a series of reference compounds present in Origanum essential oils, in order to quantify their constituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Oregano is rich in volatile compounds such as carvacrol, thymol, and monoterpenes, which exhibit different pharmacological properties such as anti-bacterial, anti-fungal, anti-viral, and anti-oxidant; it promotes vasodilatation and is hepatoprotective [ 15 ], so oregano is also used in traditional medicine and Chinese medicine to treat digestive, neurological and respiratory disorders [ 16 ]. Clinical studies have demonstrated the pharmacological potential of oregano in various properties, such as anti-diabetic and hyperlipidemic, cardioprotective and vascular, anti-inflammatory, anti-bacterial, and insecticidal [ 17 ]. Oregano can extract essential oils rich in carvacrol and thymol, a powerful natural antibiotic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oregano is rich in volatile compounds such as carvacrol, thymol, and monoterpenes, which exhibit different pharmacological properties such as anti-bacterial, anti-fungal, anti-viral, and anti-oxidant; it promotes vasodilatation and is hepatoprotective [ 15 ], so oregano is also used in traditional medicine and Chinese medicine to treat digestive, neurological and respiratory disorders [ 16 ]. Clinical studies have demonstrated the pharmacological potential of oregano in various properties, such as anti-diabetic and hyperlipidemic, cardioprotective and vascular, anti-inflammatory, anti-bacterial, and insecticidal [ 17 ]. Oregano can extract essential oils rich in carvacrol and thymol, a powerful natural antibiotic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EOs exhibit a diverse array of biological actions, including antibacterial, anti-inflammatory, antioxidant, antiproliferative and genoprotective properties. 10,11 Calamintha nepeta (Meuta or Nebta in the Algerian language) is a small aromatic perennial plant with ovals and small leaves, reaching 60 cm in height and classified as members of the Lamiaceae family, which is largely widespread in the Mediterranean region . 12,15 Traditionally, it was employed for both culinary and medicinal purposes as an antiseptic, spasmolytic, diuretic, and cough suppressant.…”
Section: Introductionmentioning
confidence: 99%